Nsambya Community Home-Based Care Complements National HIV and TB Management Efforts and Contributes to Health Systems Strengthening in Uganda: An Observational Study. (6th March 2014) - Massavon, William; Mugenyi, Levi; Nsubuga, Martin; Lundin, Rebecca; Penazzato, Martina; Nannyonga, Maria; Namisi, Charles; Ingabire, Resty; Kalibbala, Daniel; Kironde, Susan; Costenaro, Paola; Bilardi, Davide; et al.
Abstract : Community Home-Based Care (CHBC) has evolved in resource-limited settings to fill the unmet needs of people living with HIV/AIDS (PLHA). We compare HIV and tuberculosis (TB) outcomes from the Nsambya CHBC with national averages in Kampala, Uganda. This retrospective observational study compared HIV and TB outcomes from adults and children in the Nsambya CHBC to national averages from 2007 to 2011. Outcomes included numbers of HIV and TB patients enrolled into care, retention, loss to follow-up (LTFU), and mortality among patients on antiretroviral therapy (ART) at 12 months from initiation; new smear-positive TB cure and defaulter rates; and proportion of TB patients tested for HIV. Chi-square test and trends analyses were used to compare outcomes from Nsambya CHBC with national averages. By 2011, approximately 14, 000 PLHA had been enrolled in the Nsambya CHBC, and about 4, 000 new cases of TB were detected and managed over the study period. Overall, retention and LTFU of ART patients 12 months after initiation, proportion of TB patients tested for HIV, and cure rates for new smear-positive TB scored higher in the Nsambya CHBC compared to national averages. The findings show that Nsambya CHBC complements national HIV and TB management and results in more positive outcomes.